Pistols Carrying Of Ordinance to Regulate the Carrying of Pistols, Oct. 25, 1880, reprinted in BROOKLYN DAILY EAGLE (N.Y.), Oct. 26, 1880, at 1 - (:unkn) unknown (General Publisher, 1880)
Prohibited concealed carry of any pistol without a license. Licenses only issued to individuals twenty-one and over in age.
--
Keywords: CARRY - CONCEALED